A provable secure sealed‐bid multi‐attribute auction scheme under semi‐honest model. (24th June 2013) - Shi, Wenbo
SUMMARY Secure electronic auction protocol attracts increasing attention in the field of information security research. A variety of secure electronic auction protocols have achieved a lot. However, those studies mainly focus on price‐based auction model. There are few literatures involving security issues of multi‐attribute e‐auction. In recent years, the existing literatures mainly focus on the winner determination problem of multi‐attribute auction, but research of multi‐attribute e‐auction just begin from the perspective of information security. The proposal intends to start with the multi‐attribute e‐auction protocol, explores the different results in the multi‐attribute auction model because of different bid structures, focuses on qualitative attribute‐based winner determination auction model, proposes a new qualitative attribute‐based sealed‐bid multi‐attribute auction scheme under semi‐honest model for the first time. According to the security analysis and computation comparison, it provides strong bid privacy, public verifiability, and reasonable computational cost. Copyright © 2013 John Wiley & Sons, Ltd.